PENGARUH KETERAMPILAN MENGGUNAKAN VARIASI MENGAJAR GURU TERHADAP HASIL BELAJAR BAHASA INDONESIA SISWA KELAS V SD NEGERI 175758 HUTAGURGUR - B. Sarmauli Simanjuntak; Nurmayani Nurmayani; Halimatussakdiah Halimatussakdiah; Tiarnita Maria Sarjani Br. Siregar; Sri Mustika Aulia (Universitas Negeri Medan, 2026)
This study aims to analyze and describe the effect of implementing teacher skills using teaching variations on improving the learning outcomes of fifth-grade students at SD Negeri 175758 Hutagurgur in the Indonesian language subject. This research was conducted at SD Negeri 175758 Hutagurgur in the even semester of the 2025/2026 Academic Year. The type of research used was experimental research with a pre-experimental research design and a one-group pretest-posttest design. This study involved one sample group, namely the fifth-grade class, consisting of 30 students. Data collection techniques were carried out through observation, tests, and documentation. The instrument used in this study was a multiple-choice test to measure student learning outcomes. The results of the study indicate a significant and positive effect between the implementation of teaching variation skills before and after the implementation of teaching variation skills in improving fifth-grade students' Indonesian language learning outcomes. This is evident from the results of the hypothesis test, which obtained a significance value of 0.000, which is lower than the significance level of α = 0.05 (0.000 < 0.05). Therefore, H0 is rejected and Ha is accepted, indicating that teachers' teaching variation skills have an effect on improving fifth-grade students' Indonesian language learning outcomes.